2017
DOI: 10.1002/anie.201705671
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of Simple Olefins through Selective Allylic C−C Bond Cleavage: A Direct Approach to Cinnamyl Aldehydes

Abstract: A novel metal-free allylic C-C σ-bond cleavage of simple olefins to give valuable cinnamyl aldehydes is reported. 1,2-Aryl or alkyl migration through allylic C-C bond cleavage occurs in this transformation, which is assisted by an alkyl azide reagent. This method enables O-atom incorporation into simple unfunctionalized olefins to construct cinnamyl aldehydes. The reaction features simple hydrocarbon substrates, metal-free conditions, and high regio- and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 135 publications
0
10
0
Order By: Relevance
“…We previously developed oxidative nitrogenation reactions of simple hydrocarbons with DDQ as the oxidant, which suffers from its toxicity, high cost, and difficulty in the removal of DDQH 2 waste. Inspired by the above significant electrochemical C–H aminations, we therefore tried to investigate the possibility of the electrochemical C–C amination of alkylarenes.…”
mentioning
confidence: 99%
“…We previously developed oxidative nitrogenation reactions of simple hydrocarbons with DDQ as the oxidant, which suffers from its toxicity, high cost, and difficulty in the removal of DDQH 2 waste. Inspired by the above significant electrochemical C–H aminations, we therefore tried to investigate the possibility of the electrochemical C–C amination of alkylarenes.…”
mentioning
confidence: 99%
“…In the 1950s, heterolytic fragmentations were considered to be advanced methods for cleaving C­(sp 3 )–C­(sp 3 ) bonds . Until now, C–C bond cleavage reaction has made great achievements by the groups of Song and Jiao, Xu, Kakiuchi, Wei, Ouyang and Xie, Han, Hyodo, Xiao and Zhou, our work, and others . For example, in 2017, Song and Jiao et al reported an allylic C–C bond cleavage reaction of olefins to synthesis of cinnamyl aldehydes in the presence of alkyl azides, DDQ, and TFA .…”
mentioning
confidence: 84%
“…Until now, C–C bond cleavage reaction has made great achievements by the groups of Song and Jiao, Xu, Kakiuchi, Wei, Ouyang and Xie, Han, Hyodo, Xiao and Zhou, our work, and others . For example, in 2017, Song and Jiao et al reported an allylic C–C bond cleavage reaction of olefins to synthesis of cinnamyl aldehydes in the presence of alkyl azides, DDQ, and TFA . In 2018, Xu et al reported a cascade method for synthesis of enantiopure chroman-2-one and dihydrobenzofuran derivatives by the C–C bond cleavage of cyclopropenones .…”
mentioning
confidence: 97%
“…The resulting mixture was heated at reflux for 12 h. After the conversion was complete, the reaction mixture was then concentrated by evaporation. The residue was purified by silica gel column chromatography using petroleum ether/EtOAc as an eluent (PE/EA = 20:1, R f = 0.3) to give the corresponding ( E )-3-(naphthalen-1-yl)-allyl acetate 1o as a colorless oil in 66% yield …”
Section: Methodsmentioning
confidence: 99%